Knowledge and practice regarding cervical cancer prevention among women in a rural area of Tripura, India - Banik, Suranjana; Sahu, Dinesh Prasad; Bhattacharjya, Himadri (International Journal Of Community Medicine And Public Health, 2022)
Background: Cervical cancer is commonest in developing countries and the third most common form of cancer among women worldwide which presents a later stage causing high morbidity and mortality. PAP smear discovered in 1941 was a revolutionary screening test but acceptance is poor. Objective was to detect the level of awareness regarding prevention of cervical cancer among rural women and to study the determinants of awareness regarding prevention of cervical cancer. Methods:A community based cross-sectional study was conducted in rural field practice area of Agartala Government Medical College for two months among 131 women chosen by multistage sampling, aged 15 years and above. Quantitative data were collected by administering a structured interview schedule. Chi square test was applied for testing the significance of study findings and p<0.05 was considered statistically significant. Results: About 78% of the study women were primary educated and 33.3% of the study women have heard about cervical cancer and health care providers were the source of information for 34.04% of the respondents. 99.2% of the women didn’t hear about PAP smear, nor they have any idea of vaccination. They didn’t undergo any screening test and cited “absence of symptoms” as the main reason. Conclusions:Majority of the studied women didn’t have any clear idea of cervical cancer, screening and vaccination and level of awareness was very low. Intensified health educational programs should be launched. Health workers and physicians must play critical role in counselling. Information about safety, efficacy, insurance coverage etc. to be facilitated for active HPV vaccination.